A NOVEL Z-SOURCE INVERTER WITH LOW CAPACITOR VOLTAGE STRESS AND SMALL INDUCTANCE (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
In this paper author has proposed a novel approached for Z source inverter. The proposed z source network capacitor is designed to produce very minimum voltage stress than the traditional one and it possesses the capabilities like maximum limitation to inrush current while starting. Another major advantage of this system is, it can be used with wide range of load though it has very small inductor. As it has small inductor when compared with conventional z source inverter, the proposed converter has lower cost and less weight. The operating principle and various parameters are analyzed in a great detail and same is been verified with MATLAB simulink. And it has found that newly proposed z source inverter has more advantages than conventional z source converter.